2016
DOI: 10.1080/10942912.2015.1099042
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds, Antioxidant Activity, and Medium Chain Fatty Acids Profiles of Coconut Water and Meat at Different Maturity Stages

Abstract: Coconut is grown in tropical and subtropical areas worldwide. The endosperm (water and meat) is consumed and processed in different forms. This study investigated the antioxidant activities and identified the phenolic compounds existing in the water and meat of coconut fruits at three different maturity stages, i.e., 180, 190, and 225 days after pollination from two planting areas in Thailand. Total phenolic content and antioxidant activity indices increased as the coconut matured from 180 to 190 days after po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
40
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 27 publications
11
40
3
2
Order By: Relevance
“…The total phenolic content in the fresh TCW was found to be 3.75 mg GAE/100 ml, which was slightly lower than the earlier reported total phenolic content in the fresh TCW by Mahayothee et al () (5.18–7.17 mg GAE/100 ml), and by Adubofuor et al () (4.68–9.51 mg GAE/100 ml) probably due to maturity, varietal, and climatic differences. Although there was significant ( p < .05) loss in total phenolics in treated TCW when compared to fresh TCW, no significant ( p > .05) difference in phenolic content of nonthermally and heat‐treated TCW was observed during refrigerated storage.…”
Section: Resultscontrasting
confidence: 63%
“…The total phenolic content in the fresh TCW was found to be 3.75 mg GAE/100 ml, which was slightly lower than the earlier reported total phenolic content in the fresh TCW by Mahayothee et al () (5.18–7.17 mg GAE/100 ml), and by Adubofuor et al () (4.68–9.51 mg GAE/100 ml) probably due to maturity, varietal, and climatic differences. Although there was significant ( p < .05) loss in total phenolics in treated TCW when compared to fresh TCW, no significant ( p > .05) difference in phenolic content of nonthermally and heat‐treated TCW was observed during refrigerated storage.…”
Section: Resultscontrasting
confidence: 63%
“…Coconut haustorium can be used as sugar supplements. Coconut water (liquid endosperm) and meat (solid endosperm) is popular as food sources because of their benefits to human health (Yong et al, 2009; DebMandal and Mandal, 2011; Mahayothee et al, 2015). However, the knowledge about the usefulness of haustorium as food for human nutrition is still scanty.…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous fruits have antioxidant properties. [47,48] This study suggested the potential health beneficial effect of P. sylvestris fruit through prevention of formation of free radicals. The underutilized fruits of P. sylvestris could be used as a food ingredient because of the important biological activities determined during the present study.…”
Section: Antioxidant Activitiesmentioning
confidence: 78%